Resting heart rate and auditory evoked potential - Regaçone, Simone Fiuza [UNESP]; Lima, Daiane Damaris Baptista de [UNESP]; Valenti, Vitor Engrácia [UNESP]; Frizzo, Ana Cláudia Figueiredo [UNESP] (Hindawi Publishing Corporation, 2015)
The objective of this study was to evaluate the association between rest heart rate (HR) and the components of the auditory evoked-related potentials (ERPs) at rest in women. We investigated 21 healthy female university students between 18 and 24 years old. We performed complete audiological evaluation and measurement of heart rate for 10 minutes at rest (heart rate monitor Polar RS800CX) and performed ERPs analysis (discrepancy in frequency and duration). There was a moderate negative correlation of the N1 and P3a with rest HR and a strong positive correlation of the P2 and N2 components with rest HR. Larger components of the ERP are associated with higher rest HR.